Investigation of Factors Influencing the Structural Vibration in Ball Bearings - Kapil Mehra; Kambiz Farhang; Jayanta Datta (International Journal of Rotating Machinery)
Hertzian equation for elastic contact is utilized along with lumped parameter approach to obtain the equations that govern the structural vibration of ball bearings. The lumped parameter formulation is obtained by treating various elements with mass lumped at their centers of gravity and the contact as nonlinear springs with nonlinear spring rates.